IMPLEMENTASI METODE EOQ DALAM PENGENDALIAN PERSEDIAAN BAHAN BAKU DI MASA PANDEMI COVID-19 PADA GELORA CAKE - Afian Dezi Sanda Sipi (Paulus Journal of Accounting (PJA), 2022)
The study aims to know the control of the supply of rawmaterials applied to the throng cake Makassar the great mother.This type of research USES a qualitative descriptive method of dataanalysis techniques used in this study by its very own metoni EOQ.According to data from bank Indonesia the central bank's decisionto raise the bi rate by 25 basis points to 8.25 percent, he said.According to research, the application of EOQ methods can lowerboth economic and optimal supply costs and supply levels of rawmaterials than those used by makassar's Gelora Cake.